Nanosensors for a Monitoring System in Intelligent and Active Packaging - Soto-Gomez, J; Sabattin-Ortega, J; Carrasco-Armijo, R; Fuertes-Sanchez, G (Hindawi Publishing Corporation, 2016)
A theoretical wireless nanosensor network (WNSN) system that gives information about the food packaging condition is proposed. The protection effectiveness is estimated by measuring many factors, such as the existence of microorganisms, bacteria, gases, and contaminants. This study is focused on the detection of an antimicrobial agent (AA) attached on a polymer forming an active integrated package. All monitoring technologies for food conservation are analyzed. Nanobiosensor nanomachine (NM), which converts biological or chemical signals into electrical signals, is used. A mathematical model, which describes the constituent s emigration from the package to food, is programmed in MatLab software. The results show three nanobiosensors forming a WNSN. The nanobiosensors are able to carry out the average concentration for different spots in the package. This monitoring system shows reading percentages in three degrees and different colors: excellent (green), good (cyan), and lacking (red). To confirm the utility of the model, different simulations are performed. Using the WNSNs, results of AA existing in food package (FP) through time were successfully obtained. © 2016 Guillermo Fuertes et al.